The Effect of Economic Growth, Population, Human Development Index (HDI), and Poverty on Income Inequality in North Sumatra - Wulandari, Retno; Hasyim, Sirojuzilam; Rahman, Arif (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the impact of economic growth, population size, Human Development Index (HDI), and poverty on income inequality in the provinces of Sumatera Utara from 2014 to 2023. The research employs a quantitative approach using panel data regression analysis, incorporating both time-series and cross-sectional data from 33 districts/cities across the region. The findings reveal that economic growth has a significant negative effect on income inequality, indicating that higher economic growth leads to a more equitable income distribution. Conversely, population growth and poverty are found to exacerbate income inequality, with a higher population and increased poverty levels contributing to greater disparities in income across the province. Furthermore, the study finds that improvements in HDI correlate with lower income inequality, as higher educational attainment, healthcare access, and living standards contribute to increased productivity and more balanced income distribution. This research underscores the importance of inclusive economic growth and targeted poverty reduction strategies to mitigate income inequality in Sumatera Utara. The results suggest that addressing the underlying factors of population growth and poverty could significantly enhance the economic equity in the region.